2007
DOI: 10.1037/1040-3590.19.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Computer-administered interviews and rating scales.

Abstract: To evaluate the value of computer-administered interviews and rating scales, the following topics are reviewed in the present article: (a) strengths and weaknesses of structured and unstructured assessment instruments, (b) advantages and disadvantages of computer administration, and (c) the validity and utility of computer-administered interviews and rating scales. Computer-administered evaluations are more comprehensive and reliable and less biased than evaluations routinely conducted in clinical practice. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 107 publications
2
63
0
1
Order By: Relevance
“…The results of this study strengthen the argument that this clinical task is very diffi cult and highlights the assistance that a feedback system can provide. Several studies have demonstrated the benefi t that such measures can add to routine clinical judgment (Garb, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study strengthen the argument that this clinical task is very diffi cult and highlights the assistance that a feedback system can provide. Several studies have demonstrated the benefi t that such measures can add to routine clinical judgment (Garb, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of self-report instruments include economy, ease of administration, and facilitation of disclosure, because respondents are less likely to underreport socially undesirable behaviors when questions are self-administered rather than posed by an interviewer (Garb, 2007;Tourangeau & Yan, 2007). However, for antisocial individuals with tendencies to manipulate, deceive, and minimize faults, ability and willingness to accurately self-report deviant behaviors may be compromised (Lilienfeld, 1994;Whyte et al, 2006;cf.…”
mentioning
confidence: 99%
“…One might question the equality of computerized questionnaires and paper-and-pen versions. However, there are sufficient indications that they show similar psychometric properties (Carlbring et al, 2007;Garb, 2007;Schulenberg & Yutrzenka, 2001). Third, as we did not include a no-treatment group in our study, we do not know whether the modest improvements were significantly better than doing nothing.…”
Section: Discussionmentioning
confidence: 75%